2003
DOI: 10.1037/0735-7044.117.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to amphetamine hypophagia: A miscrostructural analysis of licking behavior in the rat.

Abstract: The development of tolerance to amphetamine-induced hypophagia was assessed by recording changes in lick parameters in rats given chronic administration of the drug (2 mg/kg) and access to sweetened milk. Although licking and milk intake gradually recovered, the volume of milk ingested per lick remained suppressed. Amphetamine had no effect on the interlick interval or the force per lick. In contrast, the drug caused a sustained increase in the number of lick bursts (defined by pause criteria of 0.5-2.0 s) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…However, they took longer to complete the remainder of their licks, due at least in part to an increase in the number of pauses. These results are consistent with those of a previous study, which demonstrated that tolerant rats showed an increased number of lick bursts (defined as consecutive licks separated from other licks by pauses ranging from 0.5 to 3 s) compared with saline controls (Wolgin & Jakubow, 2003a). The present results are also consistent with those of a study by Wolgin and Wade (1995) in which rats given chronic injections of amphetamine (2 mg/kg) could self-administer intraoral infusions of milk by maintaining a stationary head posture within intersecting photobeams.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, they took longer to complete the remainder of their licks, due at least in part to an increase in the number of pauses. These results are consistent with those of a previous study, which demonstrated that tolerant rats showed an increased number of lick bursts (defined as consecutive licks separated from other licks by pauses ranging from 0.5 to 3 s) compared with saline controls (Wolgin & Jakubow, 2003a). The present results are also consistent with those of a study by Wolgin and Wade (1995) in which rats given chronic injections of amphetamine (2 mg/kg) could self-administer intraoral infusions of milk by maintaining a stationary head posture within intersecting photobeams.…”
Section: Discussionsupporting
confidence: 93%
“…The rats were housed individually in stainless steel cages with wire mesh floors in a room maintained on a 12-hr light-dark cycle (lights on at 8:00 a.m.) and were fed three Purina Rat Chow pellets (about 15 g) and given water ad libitum daily in their home cages. The data for this experiment were collected as part of a larger study on the microstructure of licking in amphetamine-treated rats, some of which have been published (Wolgin & Jakubow, 2003a).…”
Section: Subjectsmentioning
confidence: 99%
“…This reduction likely arises as a consequence of shorter tongue protrusions as occurs in OFC-lesioned rats (Whishaw and Kolb 1983). To this point, almost identical changes in the microstructure of licking were found in rats chronically treated with amphetamine (Wolgin and Jakubow 2003), a drug that was found to decrease dendritic spines in pyramidal neurons in the lateral OFC (Crombag et al 2005). In summary, we found that inactivation of the OFC affects the neural circuitry related to organize licking clusters, suggesting that the OFC has a role in anticipating and modulating the clusters of rewarding gustatory stimuli.…”
Section: Effects Ofc Inactivation On the Microstructure Of Lickingmentioning
confidence: 88%
“…Analyses of the microstructure of feeding also have supported the view that amphetamine primarily disrupts the appetitive phase of feeding (Blundell & Latham, 1980;Rosofsky & Geary, 1989;Wolgin & Jakubow, 2003). For example, Wolgin and Jakubow (2003) demonstrated that amphetamine increased the number of pauses within the session, which resulted in more lick bursts and fewer licks per burst (Wolgin & Jakubow, 2003). Cumulative records from tolerant rats have revealed that, unlike undrugged controls, which complete all of their licking responses within the first 10 -15 min of the session, amphetamine-tolerant rats distribute their licking throughout the session, interspersed with pauses during which stereotyped movements occur (Wolgin & Jakubow, 2004).…”
mentioning
confidence: 87%